TINGKAT KETERAMPILAN TEKNIK DASAR BOLA VOLI PADA USIA 13-15 TAHUN PUTRA PADA KLUB BOLA VOLI TARUNA MERAH PUTIH KOTA SEMARANG TAHUN 2021 - Kristian Pradana; Catur Wahyu Priyanto; Liska Sukiyandari (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2022)
The purpose of this study was to determine the skill level of passing down, passing over, serving and smashing male athletes aged 13-15 years at the Taruna Merah Putih club, Semarang City. This study uses a quantitative descriptive approach. Sampling used purposive sampling technique, namely male athletes aged 13-15 years, totaling 20 people. The results of this study are the bottom passing that got a value of 5 there were 11 athletes (55%), who got a value of 4 there were 3 athletes (15%), who got a value of 3 there were 6 athletes (30%), who got a value of 2 and 1 were 0 athlete (0%). There were 9 athletes (45%), who got a score of 4, 5 athletes (25%), who got a score of 3, there were 3 athletes (15%), those who got a score of 2 were 3 athletes (15%) and 1 there are 0 athletes (0%). The top service that got a score of 5 was 1 athlete (5%), those who got a value of 4 were 8 athletes (40%), those who got a score of 3 were 10 athletes (50%), those who got a score of 2 were 1 athlete (5%), who get a value of 1 there are 0 athletes (0%). Smash that got a score of 5 there were 4 athletes (20%), those who got a value of 4 were 10 athletes (50%), those who got a score of 3 were 6 athletes (30%), those who got a value of 2 and 1 were 0 athletes (0%)